The application of natural dyes for natural rubber latex foam products / Nipawan Pongprom - Pongprom, Nipawan (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
In this work, we are interested in application of natural dyes in the NR latex foam productions. Three natural dyes from plant including sappan powder, turmeric powder and black galingale powder were applied in the study. They were mixed into rubber latex during foaming process. The obtained products were examined on color distribution and intensity, color sustainability to sunlight and heat, color leaching in water. The results showed that, the products mixing with sappan powder, turmeric powder and black galingale powder gave NR latex foam products in deep red, yellow and brown color, respectively. Increasing the amount of natural dyes resulted in more intensity of color with well pigment distribution. Sunlight showed strong effect on color sustainability of products mixing with sappan and turmeric powder. We suggested that absorption of UV light by chromophore in the chemical structure of pigment resulted in decomposition of pigment. Heat showed slightly effect on the color sustainability. The products mixing with sappan powder and turmeric powder showed significantly color leaching in water. The quantitative analysis by UV-vis spectroscopy showed concentration of pigment at 117, 159 and 166 ppm from product mixing with 5, 7 and 9 gram of sappan powder, respectively. At this point, we can conclude that sappan powder and turmeric powder can be applied in NR latex foam production. Various color shades can be obtained by varying amount of dyes power. However, natural dye was not stable to sunlight. They are suitable for indoor products. Moreover, study of optimal mordant should be carried out in order to increase colorfastness